واقع التدقيق الداخلي في بيئة التحول الرقمي - سعيدة ولابي; كريمة العابد; وئام باهي; لندة الحاج علي (جامعة الوادي university of eloued, 2024)
" هدفت هذه الدراسة إلى إبراز المفاهيم النظرية للتحول الرقمي من جهة ومن جهة أخرى تأثيره على التدقيق الداخلي، مع عرض لأهم مظاهر التحول الرقمي التي ساهمت في تطوير مهنة التدقيق الداخلي مثل تقنية البلوكتشين، الذكاء الاططناعي، انترنت الأشياء،.....إلخ؛ تمت الدراسة من خلال محاولة الإجابة عن الإشكالية الرئيسية: ما مدى مساهمة التحول الرقمي في الرفع من كفاءة وفعالية التدقيق الداخلي؟. تمت معالجة الموضوع من خلال شقين أحدهما نظري والآخر تطبيقي ففي الجانب النظري تم التعرف على ماهية التحول الرقمي ومختلف مكوناته وخصائصه وتقنياته التي تقدمها لمنظمات الأعمال، كما تم التطرق إلى التدقيق الداخلي وكيفية استفادته من مختلف تقنيات وآثار التحول الرقمي، أما الجانب التطبيقي فقد تم إسقاط المعرف النظرية على الواقع العملي باستخدام المنهج الوصفي التحليلي، تمثلت أداة الدراسة في استبيان موزع على عينة من ستة وأربعون فرد خبراء في مجال المحاسبة ومسيري مؤسسات اقتصادية في ولاية الوادي، وقد تم التوصل إلى أن المؤسسات تمارس التحول الرقمي وتسعى نحو تعزيز كفاءة وفاعلية عمليات التدقيق الداخلي بدرجة عالية وهذا ما جعل العلاقة بينها علاقة ارتباط طردي قوي أدى إلى التأثير بدرجة عالية على رفع كفاءة وفعالية التدقيق الداخلي. " " This study aimed to highlight the theoretical concepts of digital transformation on the one hand and on the other hand its impact on internal auditing, with a presentation of the most important aspects of digital transformation that have contributed to the development of the internal audit profession such as blockchain technology, artificial intelligence, the Internet of Things, etc. The study was conducted by trying to answer the main problem: To what extent does digital transformation contribute to increasing the efficiency and effectiveness of internal audit? The topic was addressed through two parts, one theoretical and the other applied. In the theoretical aspect, the nature of digital transformation and its various components, characteristics, and technologies that it provides to business organizations were identified. Internal audit and how it benefits from the various technologies and effects of digital transformation were also discussed. As for the applied aspect, the definition was dropped. Theory over practical reality using the descriptive analytical approach. The study tool was a questionnaire distributed to a sample of forty-six individuals, experts in the field of accounting and managers of economic institutions in the state of El Oued. It has been found that institutions are practicing digital transformation and seeking to enhance the efficiency and effectiveness of internal audit operations to a high degree, and this has made the relationship between them a strong, direct correlation that has led to a high degree of influence on raising the efficiency and effectiveness of internal auditing. "
مذكرة ماستر
Keywords: التحول الرقمي، التدقيق الداخلي، Digital Transformation; Internal Audit